2006
DOI: 10.1245/aso.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Limb Perfusion With Tumor Necrosis Factor α and Melphalan for Locally Advanced Soft Tissue Sarcoma: The Value of Adjuvant Radiotherapy

Abstract: Adjuvant EBRT reduces the risk for local recurrence after delayed resection in soft tissue sarcoma patients treated with ILP and tumor necrosis factor and is indicated when resection margins are close or microscopically positive. It also seems beneficial after an R0 resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Thijssens et al29 showed that adjuvant EBRT seems beneficial in all patients, so it might be impossible to evaluate the sole effects of ILP on the vascular system in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thijssens et al29 showed that adjuvant EBRT seems beneficial in all patients, so it might be impossible to evaluate the sole effects of ILP on the vascular system in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusions are possible [1,109], but technically not always easy to perform. Therefore, radiation therapy after delayed surgical resection following ILP has been proposed to improved local control, as retrospective studies have demonstrated a significantly lower local recurrence rate for patients receiving adjuvant radiotherapy [148,149]. Although some reports have focused on the morbidity of this combined approach [150][151][152], the only study available comparing a series of 34 consecutive patients who were either additionally treated with radiotherapy after ILP or not found no differences in treatment-related toxicity between the two groups at a median follow-up of 34 months [148].…”
Section: Ilp With Tnf and Doxorubicinmentioning
confidence: 99%
“…Excision was classified as radical (R0) when the resection margins were free of tumor cells, as R1 when resection margins were microscopically involved or as R2 in case of macroscopically involved resection margins. Postoperative external beam radiotherapy (60-70 Gy) was considered indicated in case of <95% tumor necrosis with marginal resection margins, microscopically or macroscopically involved resection margins [26]. Postoperative chemotherapy was given within European Organization for the Research and Treatment of Cancer trials (EORTC 62061 and 62931) or in a palliative setting, in case of distant metastases.…”
Section: Treatment Response and Follow-upmentioning
confidence: 99%